The Role of Self-Reflection and Peer Review in Curriculum-focused Professional Development for Teachers - Yurtseven, Nihal; Altun, Sertel (HACETTEPE UNIV, 2018)
Professional development is the backbone for teachers to sustain their professional lives without coming to a stop and they need a considerable amount of solid support in this process. The purpose of this study is to investigate what contributions self-reflection and peer review made on teachers' professional development within the scope of curriculum-focused professional studies based on Understanding by Design (UbD), an instructional design model. The study represents a threshold about providing a curriculum-focused professional development in higher education EFL teaching within the scope of a professional dialog among teachers. The study was carried out through action research. The participants of the study were 10 EFL teachers working at a state university in Istanbul, Turkey. Within the framework of the study, the teachers received training about UbD, formed groups and made unit designs and implemented them in their classes as part of the action research. As data collection tools, self-reflection and peer review forms were used. The collected data were analyzed through the content analysis. Within the context of the content analysis, the collected forms were read, coded carefully and the emerging themes were identified. The findings of the study indicated that self-reflection and peer review made considerable contributions to the teachers' professional development throughout the study. With the help of self-reflection and peer review, the teachers had the opportunity to revise their unit designs and implementation process and their awareness raised about their strengths and weaknesses.
Keywords: Understanding by Design (UbD); professional development; unit design; peer review; self-reflection; QUALITATIVE RESEARCH; Education & Educational Research